PENGARUH PEMBINAAN TERHADAP PENINGKATAN KUALITAS HIDUP PMKS DI DINAS SOSIAL, PEMBERDAYAAN PEREMPUAN, DAN PERLINDUNGAN ANAK KABUPATEN SUMEDANG - Lalas Sulastri; Ela Melawati; Inten Srinoni; Lusi Usnatul Pratiwi; Mayang Aprilianti; MIta Auliya Rahmah (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2021)
The research method used is the analysis description, with the research variable consisting of independent variables, namely coaching and the dependent variable quality of life. The study population was 33 employees of the social service. The sampling technique used simple random sampling, so the sample amounted to 33 people. Data collection techniques are carried out by documentation study and field studies through observation and questionnaires. The data were analyzed using statistical analysis with the path analysis model.This study aims to determine how well the implementation of PMKS guidance at the Social, Women's Empowerment and Child Protection Services. This is to find out how well the quality of life of Persons with Social Welfare Problems (PMKS) improves. The results of hypothesis testing showed that the determination coefficient test concluded that the influence of PMKS coaching on improving the quality of life for people with social welfare problems (PMKS) in Sumedang Regency reached 87.3%, while the remaining 12.7% was influenced by other variables that were not studied.